Pengaruh Perbandingan Bahan dengan Pelarut dan Waktu Maserasi terhadap Ekstrak Kulit Biji Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan - Widhiana Putra, I Kadek; Ganda Putra, G.P; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 2 (2020): Juni, 2020)
The cocoa beans husk contains a polyphenol compound with total phenolic compounds 5.78 percent. Waste cacao beans husk can be used more optimally by extracting, its countent of polyphenol compounds which can be used as natural antioxidants. This study aims to determine the effect of the comparison of ratio between material and solvent and maceration time on the extract of cocoa beans husk powder as a source of antioxidants and to determine the best type of ratio between material and solvent and maceration time to produce extracts of cocoa bean powder as a source of antioxidants. This experiment was disegred by using factorial randomized block design. The first factor is a ratio between material and solvent consisting of 3 levels, namely 1:10, 1:15, 1:20. The second factor is maceration time for 24, 36 and 48 hours. The data were analyzed with analysis of variance and continued with the Tukey test. The results showed that the comparison of ratio between material and solvent and maceration time had a very significant effect on yield, total phenolic and antioxidant capacity of cocoa beans husk extract. Interactions between treatments had a very significant effect on total phenolic and antioxidant capacity but did not significantly affect the yield of cocoa pod husk extract. The yield of the best cocoa beans husk powder extract was using ratio between material and solvent 1:20 and 48 hours of maceration with a yield of  14.49±0.19 percent. The best total phenolic and antioxidant capacity results were using ratio between material and solvent 1:15 and 48 hours with a total phenolic yield of 85.50±1.74 mg GAE/g and antioxidant capacity 55.18±0.22 mg GAEAC/g. Keywords : cocoa bens husk, extraction, solvent, antioxidants.